PENGARUH KEMAMPUAN PENALARAN MATEMATIKA MELALUI PENDEKATAN MATEMATIKA RELISTIK BERBANTU DERIVATIVE CALCULATOR PADA MATERI KALKULUS - Harahap, Yenni Novita; Siswadi, Siswadi (Pedagogi: Jurnal Ilmiah Pendidikan, 2023)
Mathematics is one of the mandatory subjects that must be studied in formal education in Indonesia. In mathematics lessons, the external learning process can be seen through interactions between students, learning tools and teachers. Reasoning is one of the most common thought processes for making new statements from other known statements, then making conclusions. Realistic Mathematics Education (RME) can improve students' mathematical reasoning abilities significantly better. The Derivative Calculator application is a helpful application in completing derivative calculations of mathematical functions based on step by step with explanations. through a realistic mathematical approach assisted by the Derivative Calculator, you can improve mathematical reasoning abilities. The increase is around